Regeneration ecology of the bamboo climber Flagellaria guineensis in the Transkei Coastal Forests, Eastern Cape, South Africa - Geldenhuys, C.J. (Coert Johannes) (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.